Guía didáctica ilustrada de juegos populares aplicada al área de educación física - Ramírez Ramírez, Alexis Mauricio (2023)
Popular games allow the evaluation of traditions as well as developing agility, skills, movement, strength and modes of behavior that function as an important element in motor development and in the social field. The objective of this research project was to design an illustrated didactic guide through the application of digital illustration to inform about popular games and the historical assessment that each one represents. The methodology that was applied had a qualitative approach since relevant data was collected about popular games, descriptive of the characteristics, profiles of people, groups, communities or any other phenomenon, it was possible to recognize the importance of popular games and illustration as resource to raise awareness and spread the different popular games that exist. Interviews were conducted with five historians from the city of Riobamba, it was possible to obtain the necessary information for its development. It will be extended that there is a high loss of the practice of popular games, the illustrated didactic guide of the popular games of the city of Riobamba allowed basic students to know and put into practice each of the games, the guide includes the number of participants and instructions to play the game.